Human rights - "Chitkara, M. G." (New Delhi, 1996)
The human rights violation at all levels is heinous crime against the society. The respect for human rights and world peace inextricably connected. Breach of human rights invariably disturb the world peace. Fundamental human rights and freedoms are inherent in all human kind and find expression in constitutions and legal systems throughout the world and in the international human rights instruments. The human rights are the rights that everyone equally has by virtue of "Their very humanity" and also by virtual of their being grounded in an appeal to "our human nature." Human rights are truly universal/They are not the monopoly of any one culture or of any one geographical region. The Indian courts had been ex tending the principles of the declaration and the covenants in giving relief to the socially and economically backward cit zens who do not have the wherewithal to approach the court for relief involving expenditure and delay. Human Rights
Keywords: Civil rights